2018
DOI: 10.1016/j.vetpar.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Boer goats appear to lack a functional IgA and eosinophil response against natural nematode infection

Abstract: Gastrointestinal nematodes (GIN) pose an existential threat to small ruminants such as sheep and goats (Hoste et al., 2010). The two species have evolved different strategies to minimise the threat (Hoste et al., 2008). In sheep, the immune response is the major mechanism of defence (McRae et al., 2015). The nematode Teladorsagia circumcincta is the dominant nematode in cool temperate areas of the world and possibly there is more known about the mechanisms of protective immunity to this nematode than any other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In sheep, parasite‐specific immunoglobulin A (IgA) activity and eosinophilia are negatively associated with faecal egg counts; that is high immune responses are associated with low faecal egg counts. In contrast, natural infections in Scottish Cashmere and Creole goats with predominantly Teladorsagia circumcincta and Haemonchus contortus have not shown these negative associations In addition, there was no negative association between FEC and parasite‐specific IgA activity or eosinophil responses in Boer goats in a mixed natural infection dominated by T circumcincta . In the same study, molecular modelling suggested that the IgA receptor on eosinophils was dysfunctional.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…In sheep, parasite‐specific immunoglobulin A (IgA) activity and eosinophilia are negatively associated with faecal egg counts; that is high immune responses are associated with low faecal egg counts. In contrast, natural infections in Scottish Cashmere and Creole goats with predominantly Teladorsagia circumcincta and Haemonchus contortus have not shown these negative associations In addition, there was no negative association between FEC and parasite‐specific IgA activity or eosinophil responses in Boer goats in a mixed natural infection dominated by T circumcincta . In the same study, molecular modelling suggested that the IgA receptor on eosinophils was dysfunctional.…”
Section: Introductionmentioning
confidence: 87%
“…The original McMaster technique to count nematode eggs in faeces was modified . As each faecal sample had two replicates where four McMaster chambers were used to count the nematode eggs, the number of eggs per gram (epg) of faeces was obtained by multiplying the total number of eggs counted by 25.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations